Organizational Commitment on Information Technology at the State Secretary Office of Perlis - Wan Ahmad Uzir, Hj. Wan Sulaiman (2004)
Information Technology (IT) has been extensively used by the Government to support its services to the public across a wide spectrum of government functions. Often, the public is unaware that IT is working ‘behind the scene' to deliver these services. Nevertheless, the public has benefited from increased efficiency in the use of IT, for example, faster renewal of road tax or driving license and greater convenience in paying various utility bills at One-stop Payment Centers. The significance of modern information technology to good governance and public administration is apparent as well. Taking advantage of modern information technology to improve the quality and effectiveness of government’s programs and services has been placed in a premium in many countries. It is believed that services could be delivered more easily and at less cost. In fact, effective and intelligent use of information technology has been an essential component of modern public administration. For that reason, we are try to interview with CEO Perlis State Information Technology Department to get a explanation about organization commitment on IT in Perlis State Secretary. We are also do the survey for 369 respondents of staff in Perlis State Secretary for support the research. In the question we are try to got they commitment and leader or top management commitment on IT application.